Leadership in Swedish Public Organizations: A Research Review in Education and Care - Haake, Ulrika; Lindberg, Ola; Rantatalo, Oscar; Grimm, Frida; Siljebo, Josef; Bäck, Thomas (Nordic Journal of Working Life Studies, 2022)
This article is a review of recent Swedish leadership research in two large public-sector areas: education and care. By comparing and contrasting research in these areas, we unveil the specifics and commonalities of research in public-sector leadership. We reviewed research articles from 2018 to 2020 and analyzed theories used, data-gathering methods employed, and topics researched. The results show some fundamental differences between the two areas. Compared to research on education, research on care is to a larger extent non-theoretical and is often focused on change management, quality assurance, and leaders’ roles in employee health. Conversely, studies on education are theory driven and mostly focused on leaders’ roles in learning and shared leadership. We discuss the state of Swedish public leadership research and make suggestions for mutual learning and moving forward in this research field.